Decisions and coordination of authorized remanufacturing supply chain considering power structures and carbon tax policy - Yanpei Cheng; Xiqiang Xia; Yanliang Zhang; Jingrui Zhang (Sustainable Operations and Computers)
The exponential expansion of the remanufacturing industry is propelled by a dual impetus of environmental conservation and economic advantages. Numerous original equipment manufacturers (OEMs) opt to entrust remanufacturing operations to authorized remanufacturers (ARs). Recognizing the power differences between an OEM and an AR, this paper establishes a game model based on three power structures: namely, OEM-led Stackelberg (NS model), AR-led Stackelberg (RS model) and Vertical Nash (VN model). We explore the effect of various power structures on pricing decisions and coordination in the authorized remanufacturing supply chain. Through equilibrium comparison, the following conclusions can be drawn: (1) In the RS model, the lowest authorized fee contributes to maximizing the market share of remanufactured products. However, the OEM's intellectual property is not adequately protected. In the VN model, heightened market competition will result in the lowest profit for both manufacturers. Furthermore, due to the latecomer advantage, the OEM achieves the highest profit in the RS model, while the AR earns the highest profit in the NS model. (2) In either model, implementing the carbon tax policy leads to an increase in price of both products, a decrease in the production of new products, an increase in the production of remanufactured products, and an overall reduction in carbon emissions. Notably, it is the NS model that exhibits the greatest environmental improvement. Conversely, the extent of environmental improvements in the VN and RS models depends on the consumers’ preferences for remanufactured products. (3) Through a cost-sharing contract, in which the AR collaborates with the OEM to share recycling costs, both the recovery rate of discarded products and the sales of remanufactured products increase significantly. A Pareto improvement in profits is observed when the sharing ratio exceeds a certain threshold. However, it's crucial to acknowledge that the overall profits of the supply chain do not reach the level that can be achieved through centralized decision-making. Based on this insight, a cost-sharing fixed authorized fee contract is introduced. In this arrangement, the AR compensates the OEM for its share of recycling costs by paying a fixed authorized fee, thereby facilitating supply chain coordination.